Black and white - Macaulay, David (Boston : Houghton Mifflin, 1990)
Four brief "stories" about parents, trains, and cows, or is it really all one story? The author recommends careful inspection of words and pictures to both minimize and enhance confusion.
Caldecott 1991 Medal Winner
HB Fanfare
Booklist
4.3
3-6
Keywords: Literary recreations; Literary recreations